Research Advances in the Role of Cereal Dietary Fiber in Modulating Glucose and lipid Metabolism via the Gut Microbiota-Bile Acid - DONG Hong-wang; QI Wen-tao; PENG Wen-ting; SONG Ge; FANG Wei (Liang you shipin ke-ji)
Disorders in glucose and lipid metabolism are closely linked to chronic metabolic diseases, including obesity, non-alcoholic fatty liver, hyperlipidemia and diabetes. Cereal dietary fiber, as a prebiotic, can lower blood sugar and lipid levels while promoting metabolic balance. Current research on cereal dietary fiber primarily focuses on its physicochemical properties and short-chain fatty acids metabolites. Recent studies suggest that dietary fiber intake regulates glucose and lipid homeostasis by modulating bile acid metabolism. This process is closely associated with gut microbiota. Therefore, this paper briefly reviewed the progress on the regulatory effects and mechanisms of glucose and lipid metabolism through the gut microbiota-bile acid pathway by grain dietary fiber, and provides examples of how dietary fiber from different grains (brown rice, wheat, oats, and other grains) regulates glucose and lipid metabolism. This review aims to elucidate the relationship between cereal dietary fiber, gut microbiota-bile acid interactions, and glucose and lipid metabolism. It provides new insights into how grain dietary fiber improves metabolic health and supports human well-being.